ChemInform Abstract: Aqueous Hydrofluoric Acid Catalyzed Facile Synthesis of 2, 3, 6‐Substituted Quinoxalines. Issue 11 (March 2015) - Chandra Shekhar, A.; Ravi Kumar, A.; Sathaiah, G.; Raju, K.; Srinivas, P. V. S. S.; Shanthan Rao, P.; Narsaiah, B.
Abstract The title compounds are efficiently and conveniently obtained by reaction of diamines with 1, 2‐dicarbonyl compounds using aqueous HF as catalyst and solvent under mild reaction conditions.